2006
DOI: 10.1002/anie.200600683
|View full text |Cite
|
Sign up to set email alerts
|

A Chemically Switchable Molecular Pinwheel

Abstract: The bottom-up fabrication of nanoscopic devices such as gears, [1] ratchets, [2] turnstiles, [3] switches, [4] and elevators [5] continues to attract much attention. The interest in molecular rotors in solution, [6] inside crystals, [7][8][9] and in the gas phase [10] has recently been extended to surface-mounted rotors; [11][12][13] most recently, a light-driven molecular rotor anchored to a gold surface has been demonstrated, [13] and a recent comprehensive review of artificial molecular rotors is available.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…2,3,7 Supramolecular arrays are of interest with respect to the study of energy transfer and photosynthetic mechanisms 7,8 while two-dimensional porphyrin assemblies have attracted attention for possible application as chemical sensors, in molecular electronics, or as chemically switchable 2D rotors. 3,9,10 Related to this, we recently showed that a porphyrin-functionalized silver surface exhibits ligand binding and unbinding reactions characteristic of the free metalloporphyrin 11 and showed that a well-chosen ligand can strongly alter the dynamics of adsorbed porphyrins. 10 Porphyrins have been attached to oxide surfaces for use as sensors by means of organophosphonate linkers.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…2,3,7 Supramolecular arrays are of interest with respect to the study of energy transfer and photosynthetic mechanisms 7,8 while two-dimensional porphyrin assemblies have attracted attention for possible application as chemical sensors, in molecular electronics, or as chemically switchable 2D rotors. 3,9,10 Related to this, we recently showed that a porphyrin-functionalized silver surface exhibits ligand binding and unbinding reactions characteristic of the free metalloporphyrin 11 and showed that a well-chosen ligand can strongly alter the dynamics of adsorbed porphyrins. 10 Porphyrins have been attached to oxide surfaces for use as sensors by means of organophosphonate linkers.…”
Section: Introductionmentioning
confidence: 88%
“…3,9,10 Related to this, we recently showed that a porphyrin-functionalized silver surface exhibits ligand binding and unbinding reactions characteristic of the free metalloporphyrin 11 and showed that a well-chosen ligand can strongly alter the dynamics of adsorbed porphyrins. 10 Porphyrins have been attached to oxide surfaces for use as sensors by means of organophosphonate linkers. 12 Our interest, however, lies in attaching metalloporphyrins to chemically active metal surfaces and we have reported a viable route for de-protecting and covalently attaching Mn porphyrin molecules to silver surfaces by means of four thio tethers.…”
Section: Introductionmentioning
confidence: 88%
“…Since the late 1980s several systems that exhibit thermally induced molecular rotation have been reported ͑Alvey et al, 1987;Mo, 1993;Gimzewski et al, 1998;Stipe et al, 1998b;Rao et al, 2003͒. The rotation of porphyrins has been studied quite extensively with STM ͑Hersam et al, 2000;Stöhr et al, 2001;Rao et al, 2004;Iancu and Hla, 2006;Vaughan et al, 2006;Ye et al, 2006;Wintjes et al, 2007͒. Other appealing systems are thioethers ͑Baber et al, 2008͒ and tetra-tert-butyl zinc phthalocyanine ͑Gao et al, 2008͒ on Au surfaces.…”
Section: Dynamics Of Nanoscale Molecular Assembliesmentioning
confidence: 99%
“…12 Such weakly bound systems are unlikely to be sufficiently robust for catalytic applications, however, especially in the presence of a solvent where resistance to leaching is an essential attribute.…”
Section: Introductionmentioning
confidence: 99%